Accelerated Production of White Pepper Using Integrated Mechanical and Enzymatic Solutions in an Automated Machine - M.F, Ashari; M.D, Ibrahim; A., Husaini; A, Zulkharnain (Trans Tech Publication, 2014)
The enzyme from Aspergillus versicolor A6 under solid state fermentation using agricultural waste as substrates were successfully produced by our group. Laboratory scale enzymatic retting for white pepper production was conducted using crude pectinase enzyme preparation found that decortications of green matured pepper berries were achieved after five days which is comparable to other commercial enzymes. Microbial specification and quality analyses found that retted berries meet the standards set by the International Pepper Community. This study presents a design and development of a machine which integrated mechanical and enzymatic solutions in the decortications of pepper pericarp to improve efficiency the production of white pepper berries as compared to conventional water retting method.